Study of Halal Certification for Food Products from a Sharia Law Perspective - Faruq Naufaldi Bintoro; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
Halal certification and labeling is a form of renewal that occurs in the food and public consumption sector. Halal certification and labeling on food in circulation, especially instant food, is something that actually did not exist in the past, but now its existence is something that is considered important. This paper is a conceptual research related to the study of halal certification and labeling on food in the perspective of Islamic law through the study of ayat ahkam. The results of the study show that halal certification and labeling on food can actually be viewed by returning to the basic rule in terms of food, namely "the law of origin of everything is permissible, until there is a reason that prohibits it". The verses that explain that food commands to eat halal food is good, so halal certification and labeling on food is so important today as an effort to fulfill the commandment by raising a belief and certainty in the halal of a food and a form of caution that will avoid eating food that is haram.